ANALISIS MATERI FISIKA DALAM PEMBELAJARAN IPA DI SD: KONSEP PENGUKURAN, BESARAN, DAN SATUAN - Bismi Afia; Meri Yessari; Irma Yendi; Nurhayati; Syarifuddin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Science learning in elementary schools includes basic physics concepts that serve as the foundation for students’ scientific understanding. The concepts of measurement, quantities and units, classification of quantities, the International System of Units (SI), and the use of measuring instruments are integral components of science education. This article analyzes these five components within the context of elementary science learning using a literature review approach. The findings indicate that the integrated introduction of these concepts strengthens students’ scientific process skills, develops logical thinking, and prepares them for more advanced scientific concepts. The effectiveness of learning is determined by contextual instructional strategies and intensive hands-on practice.